Efeito do lodo de esgoto em latossolo vermelho e na cultura do milho - Barbosa, Rômulo Spuri (2016)
The sewage sludge is the residue obtained from the treatment of municipal wastewater. Due to the levels of organic matter, macro and micronutrients can be destined to agriculture, by adding elements that can improve soil characteristics and consecutively the agricultural potential of crops. However, the sludges can contain high concentrations of heavy metals, which offer risks to human health and the environment. Therefore, the objective of this work was to evaluate the use of sewage sludge of sewage treatment plant of Paraguaçu - MG as agricultural input. It was conducted an experiment in pots in a completely randomized design, with six repetitions, where was planting the corn (Zea mays l.) in a Red Latosol fertilized with sewage sludge, in equivalent concentrations 0, 10, 20, 40, 80 e 160 t ha-1 on a dry basis. It was evaluated the response of the application of different doses of sewage sludge in concentrations of P, K, Ca, Mg, S, Zn, Mn, Pb, Cd, Cr, Ni, H + Al, CTC, SB, V % and heavy metals of the soil and productivity of corn. The sewage sludge studied attended the Brazilian legislation with respect to the levels of heavy metals and improved the chemical characteristics of soil, increasing their agricultural potential. The corn productivity increased with the addition of sewage sludge to soil, being the dose of 160 t ha-1 the most positive responses obtained. In addition, the sewage sludge caused no deleterious effects on the quality of soil and corn production, recommending the high potential for use in agriculture.